2011
DOI: 10.1177/0146167211410436
|View full text |Cite
|
Sign up to set email alerts
|

Two to Tango

Abstract: Four studies examined dyadic collaboration on quantitative estimation tasks. In accord with the tenets of "naïve realism," dyad members failed to give due weight to a partner's estimates, especially those greatly divergent from their own. The requirement to reach joint estimates through discussion increased accuracy more than reaching agreement through a mere exchange of numerical "bids." However, even the latter procedure increased accuracy, relative to that of individual estimates (Study 1). Accuracy feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 27 publications
3
33
1
Order By: Relevance
“…For example, previous research finds that signals of an advisor's expertise increase people's willingness to rely on her advice, but that in general people give less weight to advice than they should (e.g., Liberman, Minson, Bryan, & Ross, 2012;Minson, Liberman, & Ross, 2011). We suggest that in addition to assessing the accuracy of advice, people consider whether the advisor has the right to offer an opinion -and they respond with anger and derogation if she lacks this right (Study 2).…”
Section: Implications For Advicementioning
confidence: 82%
See 1 more Smart Citation
“…For example, previous research finds that signals of an advisor's expertise increase people's willingness to rely on her advice, but that in general people give less weight to advice than they should (e.g., Liberman, Minson, Bryan, & Ross, 2012;Minson, Liberman, & Ross, 2011). We suggest that in addition to assessing the accuracy of advice, people consider whether the advisor has the right to offer an opinion -and they respond with anger and derogation if she lacks this right (Study 2).…”
Section: Implications For Advicementioning
confidence: 82%
“…As Study 1's results showed, the same experience that provides a person with expertise can also make her disentitled to offer advice. Thus, people may fail to follow good advice not only because they underestimate the advisor's knowledge relative to their own (Liberman et al, 2012;Minson et al, 2011), but also because they perceive her as disentitled to advise.…”
Section: Implications For Advicementioning
confidence: 99%
“…Moreover, participants tend to mix two aggregation strategies-choosing and averaging. They alternate between ignoring advice, occasionally averaging, and more rarely fully adopting it (Minson et al, 2011;Soll & Larrick, 2009). Although this pattern of mixing averaging and ignoring advice yields a mean WOA of around 30%, it is worse for accuracy than consistently shifting 30% of the way toward advice (Soll & Larrick, 2009). 3.3 | Moderators of advice taking 3.3.1 | Accuracy, confidence, and trust…”
Section: Accuracy and Averagingmentioning
confidence: 99%
“…People tend to discount the opinions of others, with average weights of 70% on their own estimate and 30% on the advice (Harvey & Fischer, 1997;Yaniv & Kleinberger, 2000). Notably, this average weight arises from a multi-modal distribution of weights in which people often ignore advice entirely, occasionally average, and more rarely fully accept advice (Minson, Liberman, & Ross, 2011;Soll & Larrick, 2009;Soll & Mannes, 2011). A number of moderators of advice taking have also been identified.…”
Section: Introductionmentioning
confidence: 99%